The Effect of Giving Red Ginger Jelly an Dysmenorrhea Pain in Female Students at Junior High School in Samarinda - Lushinta, Lidia; Ratanto, Ratanto; Jasmawati, Jasmawati; Yesi, Pina; Haloho, Cristinawati B/R; Sinaga, Elisa Goretti; Sholikah, Imroatus; Nurachma, Evy; Patty, Fara Imelda Theresia (MEDFARM: Jurnal Farmasi dan Kesehatan, 2025)
Adolescence is a period of growth and developmental change, both biologically, cognitively, and psychosocially, called puberty. A sign that a teenager is experiencing puberty is that she will experience menstruation. Menstrual pain, commonly known as dysmenorrhea, occurs during menstruation. Dysmenorrhea is pain during menstruation that is felt in the lower abdomen to pain in the waist. One treatment with non-pharmacological therapy to reduce dysmenorrhea pain during menstruation is the administration of Red Ginger Jelly, which contains essential oils and aloricin, which can inhibit prostaglandin hormones to decrease pain. To determine whether Red Ginger Jelly affects dysmenorrhea pain in junior high school students in Samarinda. One group with a pre- and post-test design comprised students in 7th, 8th, and 9th grades of Junior High School in Samarinda who experienced primary dysmenorrhea pain. The non-probability sampling technique with Purposive Sampling included 18 individuals. Data were processed by univariate and bivariate analyses using the Shapiro–Wilk and Wilcoxon tests. The results of the study showed that there was an effect of giving Red Ginger Jelly on dysmenorrhea pain in students at Junior High School in Samarinda (p-value 0.000) with p value < 0.05. Red Ginger Jelly reduced primary dysmenorrhea pain in junior high school students in Samarinda.